Poetiche dell'invisibile. Il rimosso nel cinema documentario italiano contemporaneo (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
The theoretical reflection on Italian contemporary documentary focuses mainly on the expression of the visible. The present essay, instead, aims to investigate the invisible, what is not seen and the motivations behind these absences. What forms of selective iconoclasm operate in our cinema of the real, and why? Some absences are more visible and explicit, such as that of childhood for example. Others, instead, are more subtle and deceptive, as that of the city, which is apparently a widely discussed topic, but is never fully told and understood in its elusive complexity.